An Alternative Power Supply System During Peak Loads Using Solar Cells - Zulfikar, Zulfikar; Zulhelmi, Zulhelmi; Mulyadi, Agus (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Utilization of renewable energy becomes a necessity in the future due to the fossil energy supply continues to decline. In Indonesia, the use of electricity from renewable sources is minimal. The utilization of solar energy in Indonesia is still limited to remote areas or islands. The main problem of electricity in Indonesia, especially in the city of Banda Aceh, is the frequent occurrence of power outages from the state power plant (PLN), especially during peak load time (WBP). Outside of that time, electricity supply exceeds demand. This study aims to utilize solar energy to reduce the electricity consumption of PLN during WBP. The system is designed to divert the power supply from PLN to the solar power plant (PLTS). The results of a survey of 10 A (current limit) customers are used as a reference to calculate PLTS capacity. During WBP, PLTS supplies to the load, beyond that time, PLN will supply the load. The system is designed to store maximum energy beyond the WBP period into the battery, the source of energy is mainly from the PLTS and alternatively from the PLN when the PLTS can not supply the maximum power. Based on battery energy, the system diverts the load supply from PLN when the battery energy is below the recharge limit. In the case of 10 A customers, with the energy requirement during WBP of 4.3 kWh, it requires 12 solar panels (160 Watt maximum power) arranged in parallel. Thus, the system needs three batteries with 150 Ah capacity also assembled in parallel. The implementation results prove that the PLTS can store solar energy to the battery properly, the system also successfully divert the PLTS source to the load at the time of WBP and transfer back to the PLN source when the battery energy is less than the recharge limit.